The Relationship of Compressive Strength and Chemically Bound Water Content of High-Volume Fly Ash-Cement Mortar - Chunping Gu (MDPI AG, 2021)
Fly ash (FA) has been widely used in cement-based materials, but limited work has been conducted to establish the relationship between the compressive strength and hydration process of high-volume FA (HVFA)-cement-based material. In this study, the compressive strength and chemically bound water contents of FA-cement-based materials with different water-to-binder ratios (0.4, 0.5, and 0.6) and FA contents (0%, 30%, 40%, 50%, 60%, and 70%) were tested. Replacing more cement with FA reduced the compressive strength and of HVFA-cement-based materials. The compressive strength and chemically bound water content reduced by about 60–70% when 70% cement was replaced by FA. Water-to-binder ratio showed more significant influence on the chemically bonded water at later ages than that at early ages. Based on test results, the prediction equation of chemically bound water content was established, and its accuracy was verified. The error was less than 10%. The relationship between the compressive strength and chemically bound water content was also fitted. The compressive strength and chemically bound water content showed linear relationships for different water-to-binder ratios, hence the compressive strength of HVFA-cement mortar could be predicted with the chemically bound water content and water-to-binder ratios. The results of this study could be used for the prediction of the compressive strength development of HVFA-cement mortars, and is helpful to develop the mix design method of HVFA-cement-based materials.